MANAGEMENT STATUS OF TUNA (THUNNUS SP.) FISHERIES IN SANGIHE ISLANDS REGENCY USING THE ECOSYSTEM APPROACH TO FISHERIES MANAGEMENT (EAFM) - Medea, Johanis Johniforus; Yuliana, Ernik; Anwar, Kasful (Departemen PSP IPB, 2025)
Indonesia has been a pioneer in sustainable tuna management, so the ecosystem approach to fisheries management (Ecosystem Approach to Fisheries Management, EAFM) is considered vital. One of the potential areas for tuna fishing is the Sangihe Islands Waters. An assessment utilizing the Ecosystem Approach to Fisheries Management (EAFM) methodology was conducted to determine the management status of the tuna fishery in Sangihe Island Regency. The evaluation focused on indicators across six domains: institutional, economic, social, fishing technology, habitat, and ecosystems, as well as fisheries resources. By improving the composite index, the flag model approach was used to multi-criteria analysis. With a score of 67, the research indicates that the tuna fisheries management status in Sangihe Island Regency is in the Good category. Indicators in the social, ecological, and habitat domains identified problem areas that urgently require repair. The fisheries resources domain aggregate status (very good) indicated that tuna are in very good condition, and there is a reliable supply of them, supporting the very good status in the fishing techniques, economic, and institutional domains, which relate to the welfare of fishing communities. Improving tuna fisheries management in Sangihe requires focusing on habitat and ecosystem health, preventing heavy metal pollution, and actively involving stakeholders in decision-making. Engaging the community, enhancing monitoring, and preserving local knowledge are key to balancing resource use and environmental conservation. Key words: EAFM, fisheries management, Sangihe island, tuna fisheries